The PRO GREENS intervention in Finnish schoolchildren – the degree of implementation affects both mediators and the intake of fruits and vegetables. Issue 7 (8th August 2014) - Lehto, Reetta; Määttä, Suvi; Lehto, Elviira; Ray, Carola; te Velde, Saskia; Lien, Nanna; Thorsdottir, Inga; Yngve, Agneta; Roos, Eva
Abstract : Little is known about the mediating effects of the determinants of fruit and vegetable (FV) intake in school-based interventions that promote FV intake, and few studies have examined the impact of the degree of implementation on the effects of an intervention. The present study examined whether the degree of implementation of an intervention had an effect on children's fruit or vegetable intake and determined possible mediators of this effect. The study is part of the European PRO GREENS intervention study which aimed to develop effective strategies to promote consumption of fruit and vegetables in schoolchildren across Europe. Data from 727 Finnish children aged 11 years were used. The baseline study was conducted in spring 2009 and the follow-up study 12 months later. The intervention was conducted during the school year 2009–2010. The effects were examined using multilevel mediation analyses. A high degree of implementation of the intervention had an effect on children's fruit intake. Knowledge of recommendations for FV intake and liking mediated the association between a high degree of implementation of the intervention and an increase in the frequency of fruit intake. Knowledge of recommendations for FV intake and bringing fruits to school as a snack mediated the association between a low degree of implementation of the intervention and an increase in the frequency of fruit intake. Overall, the model accounted for 34 % of the variance in the change in fruit intake frequency. Knowledge of recommendations acted as a mediator between the degree of implementation of the intervention and the change in vegetable intake frequency. In conclusion, the degree of implementation had an effect on fruit intake, and thus in future intervention studies the actual degree of implementation of interventions should be assessed when considering the effects of interventions.